2018
DOI: 10.1111/1759-7714.12649
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of calcium‐binding protein S100A8 and S100A9 expression in non‐small cell lung cancer

Abstract: BackgroundThe purpose of this study was to evaluate the correlation between calcium‐binding protein S100A8 and S100A9 expression in non‐small cell lung cancer (NSCLC) and patients’ clinical features.MethodsFifty‐two NSCLC patients who underwent surgery at Zhejiang Hospital from February 2014 to January 2016 were included in this study. Calcium‐binding protein S100A8 and S100A9 expression patterns in cancer and para‐cancer tissues were examined by immunohistochemistry assay. The correlation between calcium‐bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
(24 reference statements)
1
18
0
Order By: Relevance
“…Previous studies reported differential expression of S100A9 in non-small cell lung cancer [11], breast cancer [12,13], gastric cancer [14], and colorectal cancer [15] by immunohistochemistry, consistent with the results of the present immunohistochemistry and microdissection-based mRNA analyses of OS and normal bone tissues. Therefore, differential expression of S100A9 in OS and normal tissues suggests that quantitative analysis of S100A9 mRNA levels in OS may be a promising modality for detecting OS.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported differential expression of S100A9 in non-small cell lung cancer [11], breast cancer [12,13], gastric cancer [14], and colorectal cancer [15] by immunohistochemistry, consistent with the results of the present immunohistochemistry and microdissection-based mRNA analyses of OS and normal bone tissues. Therefore, differential expression of S100A9 in OS and normal tissues suggests that quantitative analysis of S100A9 mRNA levels in OS may be a promising modality for detecting OS.…”
Section: Discussionsupporting
confidence: 92%
“…20 Proteins in the S100 family are involved in the regulation of a number of cellular processes, such as cell cycle progression and differentiation. 21 Previous studies have revealed that elevated S100A7 is associated with tumor aggressiveness and metastasis. [22][23][24] Hu et al reported that S100A7 expression is significantly increased in lung cancer, and is associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…S100A7 is a calcium‐binding protein that belongs to the S100 family . Proteins in the S100 family are involved in the regulation of a number of cellular processes, such as cell cycle progression and differentiation . Previous studies have revealed that elevated S100A7 is associated with tumor aggressiveness and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…S100A9 is a posttranslation-modified, calciumbinding protein with multiple ligands that is involved in the pathogenesis of inflammatory events and the initial development of cancer cells [16][17][18][19]. According to the previous reports, S100A9 is associated with poor overall survival of non-small-cell lung cancer (NSCLC) patients [20,21]. TGF-β signaling has been shown to cooperate with S100A9 to influence cancer metastasis [22,23]; NF-κB binds to the S100A9 promoter and activates reactive oxygen species-dependent signaling pathways, protecting hepatocellular carcinoma cells from the apoptotic death [24].…”
Section: Discussionmentioning
confidence: 99%